2023
DOI: 10.58258/jisip.v7i1.4507
|View full text |Cite
|
Sign up to set email alerts
|

The Role Of Social Media On Students’ English Vocabulary Achievement

Abstract: The purpose of this study is to explain the extent of the role of social media on students' English vocabulary mastery and also to describe the role of social media on students' vocabulary acquisition related to their respective use of social media. It uses the case study method. The data needed for this study were collected from student observations and questionnaires. Data were collected from direct observation and analyzed using descriptive qualitative methods to find out how to explain social media activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
2
1
0
Order By: Relevance
“…The learners' limitations of social media involve privacy violation, exposure to harmful content, low-level of security, cyberbullying, distraction and excessive comfort whereas the learning limitations include questioning the effect of a learning pedagogy, time consumption, lack of training and guidance and finally reliability of information. These findings confirm those of previous studies such as Khan, Ayaz and Faheem (2016), Mamudi and Alamry (2022), Ichara Sinta (2022) and Hanan, Yuliani and Suadiyatno (2023).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The learners' limitations of social media involve privacy violation, exposure to harmful content, low-level of security, cyberbullying, distraction and excessive comfort whereas the learning limitations include questioning the effect of a learning pedagogy, time consumption, lack of training and guidance and finally reliability of information. These findings confirm those of previous studies such as Khan, Ayaz and Faheem (2016), Mamudi and Alamry (2022), Ichara Sinta (2022) and Hanan, Yuliani and Suadiyatno (2023).…”
Section: Discussionsupporting
confidence: 93%
“…Mamudi and Alamry (2022) investigated learners' perception with regard to using Instagram in learning English vocabulary. Hanan (2023) investigated the role of social media in improving students' vocabulary achievement. Pham, Van Nguyen and Cao (2023) investigated the use of social media in learning English language vocabulary for Vietnamese university students.…”
mentioning
confidence: 99%
“…Those tests revealed that the social media had a significant impact in enhancing the vocabulary of the students who learned English language. This result similar with the research conducted by Hanan et al (2023) which reported that social media was crucial to learning English because it gave students who were learning the language the chance to get better at writing, reading, and other skills as well as to expand their vocabulary by reading new texts and phrases since this was the crucial media as a communication tools in the new globalization period.…”
Section: Figure 16 | the T-test Of Pretest And Posttest In Control Groupsupporting
confidence: 88%